The association Malnutrition-Inflammation Score with chronic kidney disease-associated pruritus and quality of life in hemodialysis patients: a multicenter cross-sectional study - Hossein Bavi Behbahani; Meysam Alipour; Ahmad Zare Javid; Hamidreza Razmi; Pardis Tofighzadeh; Fatemeh Fayazfar; Sara Keramatzadeh; Shiva Shokri; Haleh Soltaniyan Dehkordi; Kian Khosravi; Siavash Babajafari Esfandabad; Shokouh Shayanpour (Scientific Reports)
Abstract Malnutrition is prevalent among hemodialysis patients, negatively impacting their quality of life (QoL) and chronic kidney disease-associated pruritus (CKD-aP). This study investigates the association between the Malnutrition-Inflammation Score (MIS) and CKD-aP, as well as QoL, in hemodialysis patients. This cross-sectional study was conducted on 479 HD patients (279 males and 200 females) referred to eight dialysis centers. A food frequency questionnaire (FFQ), Kidney Disease Quality of Life Short Form (KDQOL-SF™), and Yosipovitch Itch Questionnaire (YIQ) were used to assess nutritional status, QoL, and CKD-aP, respectively. Anthropometric indices, body mass index (BMI), biochemical parameters, and adequacy of dialysis (Kt/V) were also measured in all patients. Significant differences were observed across MIS quartiles in terms of age, dialysis vintage, dialysis time, and urine volume (p < 0.05 for all). QoL scores showed significant differences, with the physical component score and symptoms/problems score being lower in higher MIS quartiles (p < 0.05 for all). Multivariate analyses revealed that higher MIS quartiles were significantly associated with worse QoL scores, including symptoms/problems and physical component scores, even after adjusting for confounders (p < 0.05 for all). Moreover, the pruritus VAS score, as well as the burden of kidney disease and mental component, had a significant negative association with MIS after adjusting for confounders (p < 0.05 for all). This study demonstrates that higher MIS, indicating poorer nutritional status, is associated with impaired QoL, particularly in the symptoms/problems, physical, and mental components among hemodialysis patients. However, no significant association was found between MIS and CKD-aP.